2016
DOI: 10.12799/jkachn.2016.27.4.337
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with Unintentional Injuries to Korean Adolescents at School: A Multilevel Study

Abstract: Purpose: This study aims at identifying individual-and school-level factors associated with unintentional injuries to Korean adolescents at school by applying multilevel modeling. Methods: From the database of the eleventh Korea Youth Risk Behavior Web-based Survey (KYRBS), the researchers selected 68,043 adolescents from the 7 th to the 12 th grades. Data were analyzed using x 2 test for prevalence and multilevel modeling for related factors of unintentional injuries at school. Results: About 22.9 percent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Consistent with other studies conducted among adolescents [ 15 , 20 , 22 , 26 ], the present study reported that participating in physical education at school was associated with higher odds of one or multiple injuries. As explained by Carmeli et al [ 38 ], lack of sufficient warm-up, poor playing grounds, unsuitable outfits, lack of safety precautions, and high extraneous exercises that have a high mechanical impact could account for the reported injuries among students who partake in physical education.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with other studies conducted among adolescents [ 15 , 20 , 22 , 26 ], the present study reported that participating in physical education at school was associated with higher odds of one or multiple injuries. As explained by Carmeli et al [ 38 ], lack of sufficient warm-up, poor playing grounds, unsuitable outfits, lack of safety precautions, and high extraneous exercises that have a high mechanical impact could account for the reported injuries among students who partake in physical education.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence suggests that factors such as sociodemographic characteristics (male sex and low socioeconomic status) [ 14 , 17 , 18 , 19 , 20 , 21 , 22 ] substance use (alcohol, tobacco, smoking, drugs) [ 2 , 14 , 15 , 18 , 20 , 21 , 23 , 24 , 25 , 26 ], soft drinks consumption, physical education at school [ 15 , 20 , 22 ], psychological distress [ 15 , 20 , 22 , 23 ], being bullied [ 2 , 18 , 19 , 23 ], engaging in physical fight [ 2 , 18 , 19 , 25 ], truancy [ 14 , 20 , 22 , 25 ], ever had sex [ 20 , 21 ], depression [ 14 ], loneliness [ 14 , 24 , 25 ], and parental or guardian support and bonding [ 20 , 22 ] are associated with unintentional injuries among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Yu-Jung Ok and Kim Myo Sung's study among 68,043 adolescents from 7 th to 12 th -grade findings show 22.9% of the adolescents had treatment experiences for unintentional injuries at school in the past 12 months and the significant factors associated with unintentional injuries at school included gender, grade, academic achievement, current smoking, alcohol consumption, frequency of high caffeine intake, depression, and relief of fatigue after sleep. [16] Fernandez et al on evaluating the Spanish National Health Survey highlighted boys suffered unintentional injuries 1.64 more times than girls (OR = 1.64; 95% CI 1.48-1.82) and adolescents aged 15-18 years (OR = 1.24; 95% CI 1.07-1.42) had a higher probability of reporting an unintentional injury when compared to children aged 6-10 years. [17] Shi et al on conducting a cross-sectional study in three main colleges in Wenzhou, China found falls were the leading cause of unintentional injury, followed by traffic injuries, animal/insect bites, and male students were more likely to be injured than female students [18].…”
Section: Discussionmentioning
confidence: 98%
“…[18] The variables that did not appear to be directly related to the occurrence of the injury or that did not show any statistical correlation were excluded. Finally, based on literature evidence [19] and the expert opinion of the investigators, three items were selected that likely have a direct impact on the incidence of injury: 1) current alcohol consumption (cAlc) defined as alcohol intake more than once within the last 30 days (excluding alcohol use related to ancestral rites or sacraments); 2) victims of violence or bullying (VicVB) defined as being treated by a doctor for physical violence within 12 months; and 3) having undergone formal education on injury prevention (Edu-IP) defined as safety education (about danger and preventive behaviour, first aid, and emergency evacuation and rescue) at school more than once within 12 months. The first two variables were risk behaviours, while the third was considered preventive behaviour.…”
Section: Methodsmentioning
confidence: 99%